2011
DOI: 10.1128/iai.01042-10
|View full text |Cite
|
Sign up to set email alerts
|

Migratory Activation of Primary Cortical Microglia upon Infection with Toxoplasma gondii

Abstract: Disseminated toxoplasmosis in the central nervous system (CNS) is often accompanied by a lethal outcome.Studies with murine models of infection have focused on the role of systemic immunity in control of toxoplasmic encephalitis, while knowledge remains limited on the contributions of resident cells with immune functions in the CNS. In this study, the role of glial cells was addressed in the setting of recrudescent Toxoplasma infection in mice. Activated astrocytes and microglia were observed in the close vici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 40 publications
0
81
0
Order By: Relevance
“…However, strong immunoreactions were observed at 30 days post-infection, as at 10 days post-infection, and a comparison of the histopathological findings called into question the occurrence of reactivation. Microglia/macrophages might be responsible for both recurrent and systemic T. gondii infections, with tachyzoites and bradyzoites hidden in the cells acting as a "Trojan horse" (Da Gama et al, 2004;Barragan and Hitziger, 2008;Dellacasa-Lindberg et al, 2011). In the present study, the strong NO immunopositivity observed in the microglia/ macrophages suggested that bradyzoites were hidden in these cells, thus providing a putative explanation for the activation of the cerebral immune mechanism.…”
Section: Discussionmentioning
confidence: 60%
“…However, strong immunoreactions were observed at 30 days post-infection, as at 10 days post-infection, and a comparison of the histopathological findings called into question the occurrence of reactivation. Microglia/macrophages might be responsible for both recurrent and systemic T. gondii infections, with tachyzoites and bradyzoites hidden in the cells acting as a "Trojan horse" (Da Gama et al, 2004;Barragan and Hitziger, 2008;Dellacasa-Lindberg et al, 2011). In the present study, the strong NO immunopositivity observed in the microglia/ macrophages suggested that bradyzoites were hidden in these cells, thus providing a putative explanation for the activation of the cerebral immune mechanism.…”
Section: Discussionmentioning
confidence: 60%
“…Intracerebral inflammation can also contribute to the onset of seizures [84]. Given the significant number of activated microglia and astrocytes in Toxoplasma- infected brains [85], parasite-induced inflammation could contribute to seizures in infected mice. Overexpression of several cytokines that are upregulated by infection (e.g.…”
Section: Neurological Complications During Toxoplasmic Encephalitismentioning
confidence: 99%
“…A molecule secreted by Toxoplasma gondii, cyclophilin 18, interacts with the chemokine receptor CCR5 and this results in the production of nitric oxide (NO), interleukin 12 (IL-12), and tumor necrosis factor α (TNFα) as well as attraction of macrophages to the site of infection to increase the chances of parasite-leukocyte interaction 36 , 37 . Once the parasite has invaded the immune cells it increases their motility and migratory activities via a G i -protein coupled receptor signaling pathway 38 - 40 . How the parasite activates the G i -protein coupled receptor signaling pathway is still not known.…”
Section: Parasite-derived Factors That Promote Bbb Crossing By Parasitesmentioning
confidence: 99%